2019
DOI: 10.1111/1346-8138.15071
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of alitretinoin depending on the concomitant use of topical corticosteroids in chronic hand eczema patients

Abstract: Alitretinoin is the only systemic agent approved for the treatment of severe chronic hand eczema (CHE) unresponsive to potent topical corticosteroids. Clinical trials have shown the efficacy of oral alitretinoin with topical emollients for CHE treatment, but most studies have failed to reach a therapeutic success rate of 50%. Reasonably, we thought it would be more effective to combine topical corticosteroids with oral alitretinoin, but the concomitant use of topical corticosteroids has not been studied yet. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…Oral alitretinoin, a 9- cis -retinoic acid, is widely used as a treatment of choice for CHE. Recently, Cheon et al [23] have revealed the clinical improvement by 44% reduction of the mTLSS following the administration of alitretinoin for an average 15 weeks. Also, a meta-analysis [10] concluded that 50% of the patients had a good percentage of clearance at a high dose of alitretinoin for 24 weeks.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Oral alitretinoin, a 9- cis -retinoic acid, is widely used as a treatment of choice for CHE. Recently, Cheon et al [23] have revealed the clinical improvement by 44% reduction of the mTLSS following the administration of alitretinoin for an average 15 weeks. Also, a meta-analysis [10] concluded that 50% of the patients had a good percentage of clearance at a high dose of alitretinoin for 24 weeks.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The efficacy of systemic treatment with alitretinoin was found to be enhanced with the addition of topical corticosteroids. 157 Allergic contact dermatitis caused by a topical corticosteroid, or its vehicle, is not uncommon and should be considered when HE does not respond to topical treatment. 158 Intermittent dosing may reduce the risk of skin atrophy, but little evidence supports this.…”
Section: Topical Corticosteroidsmentioning
confidence: 99%
“…It is a retinoid with anti-proliferative, anti-inflammatory, and immunomodulatory but not immunosuppressive effects 43 44 . The time to response was significantly shorter with alitretinoin 30 mg than 10 mg, and when combined with a topical corticosteroid, the result was clinically rapid and superior to alitretinoin monotherapy 9 45 . Since relapses were successfully treated with re-administration of alitretinoin 46 , intermittent use of alitretinoin could be suitable for long-term management of chronic hand eczema.…”
Section: Resultsmentioning
confidence: 93%